Streiks und die Zuverlässigkeit der Verkehrsbedienung - Manfred Boltze; Alexander Eisenkopf; Hartmut Fricke; Markus Friedrich; Hans-Dietrich Haasis; Günter Knieps; Andreas Knorr; Kay Mitusch; Stefan Oeter; Franz Josef Radermacher; Gernot Sieg; Jürgen Siegmann; et al. (Wirtschaftsdienst, 2016)
Mit der Privatisierung und der Aufhebung des Prinzips der Tarifeinheit haben die Arbeitskämpfe im Verkehrswesen stark zugenommen. Die Zuverlässigkeit der Verkehrsbedienung ist gefährdet und unbeteiligte Dritte haben oft das Nachsehen. Der Wissenschaftliche Beirat beim Bundesminister für Verkehr und digitale Infrastruktur hat eine Stellungnahme vorgelegt, die Empfehlungen ausspricht, wie das Streikrecht im Verkehrswesen neu geregelt werden kann. – – Of late, Germany has been hit by unprecedented strike actions by airline and railway staff. Lufthansa's pilots staged 13 walkouts between April 2014 and September 2015, resulting in the cancellation of 8,500 flights and affecting around one million passengers. The one week strike by Lufthansa's cabin crews in November 2015 forced the company to cancel another 4,700 flights. The trend towards industrial action in the German transportation sector is not limited to airline pilots and cabin crew, however. In addition, security agents and ground staff at several airports have gone on strike, and most of all, train drivers walk out with increasing frequency. In this article, measures are proposed to balance the legal, and legitimate, right of workers to use strikes as a tool of last resort in wagebargaining processes with the no less important right of customers to have access to reliable transportation services. While many other Western countries have regulations in place for the conduct of wage bargaining, including rules on work stoppages in core public service sectors, no such rules exist in Germany.
Keywords: J5; K31; L93; 330; Verkehr; Arbeitskampf; Deutschland